Can Priming Legal Consequences and the Concept of Honesty Decrease Cheating During Examinations? - Wu, Yu-Wei; Zhong, Lu-Lu; Ruan, Qian-Nan; Liang, Jing; Yan, Wen-Jing (Frontiers in Psychology, 2020)
Cheating on exams is a very common phenomenon that causes great harm. Various measures, such as chastisement and direct punishment, have been employed to reduce cheating. Previous studies have found that increasing punishment and activating “self-concept maintenance” can reduce this behavior. This study employed a priming paradigm to investigate whether priming legal consequences and the concept of honesty would reduce cheating in examination situations. We found a situation where students are traditionally cheating in examinations where we can conduct a field study. In Exp. 1, a total of 402 freshmen from 17 classes were included in this study. The 185 students in experimental condition were primed for legal consequences. We defined the cheating behaviors and employed analysts to count the number of cheaters. The results show that the number of students cheating in the primed group did not decrease compared to those in the controlled condition. In Exp. 2, A total of 339 freshmen from 14 classes participated in this experiment. The 171 students in experimental condition were primed for the concept of honesty. The results also show that about half of the students cheated in the examination, and the number of students cheating in the primed group did not decrease. This study shows that priming legal consequence and the concept of honesty were not significant in certain situations, such as during examinations. We suggest that some psychological manipulations in decreasing dishonesty behaviors should be further tested in ecological situations.